8C.07: DETECTION OF FREE-CIRCULATING DNA IN PATIENTS WITH ALDOSTERONE PRODUCING ADENOMA. (June 2015) - Cangiano, D.; Ceolotto, G.; Caroccia, B.; Citton, M.; Seccia, T.H.; Rossi, G.P.
Abstract : Objective: Tumor cells undergoing apoptosis or necrosis release cell-free DNA fragments (cf-DNA) of different sizes into the bloodstream. Primary aldosteronism (PA) caused by aldosterone-producing adenoma (APA), but not by bilateral hyperplasia (BAH), has somatic mutations in KCNJ5 gene. Hence, the detection of KCNJ5 mutations in cf-DNA from peripheral blood could allow pinpointing PA patients with APA that must be submitted to Adrenal Vein Sampling (AVS). The aim of the study was to investigate the feasibility of using cf-DNA to detect KCNJ5 mutations in plasma of PA patients. Design and method: Plasma was collected from the right/left adrenal veins from 6 APA patients undergoing AVS. Plasma from 7 patients with stomach cancer and from 6 healthy subjects was used as positive/negative control, respectively, for cf-DNA quality. The integrity index (DII) was calculated as a ratio of 400pb/200pb amplicons. A DII cut off equal or greater than 1.0 was assumed to denote cf-DNA integrity. DNA sequences entailing the region with KCNJ5 gene mutations (G151R, L168R, T158A) were amplified using PCR real time (qPCR) to obtain long (400 bp) and short (200 bp) fragments. Results: The DII for KCNJ5 amplicons on average was consistently > 1.0 in gastric cancer samples, 1.0 in healthy subjects whereas it was < 1.0 in APA patients. The cf-DNA concentration of KCNJ5 amplicons was 10-fold higher in gastric cancer patients than in AVS plasma (4.8 ± 1 vs 0.4 ± 0.1 ng/ul p < 0.01). The latter showed no significant differences between the APA and the contralateral side (0.41 ± 0.1 vs 0.36 ± 0.1). Conclusions: These results confirm the feasibility of isolating cf-DNA not only from patients with malignancies, but also with PA. With current technology the cf-DNA amount and integrity that were obtained suggest the feasibility of using this strategy to detect malignancies. However, at present the results obtained in this study do not support the use of this approach to pinpoint PA with APA based on identification of KCNJ5 mutations. Therefore, further work is needed to develop this innovative and non-invasive strategy that could be useful to pinpoint the patients with APA before the AVS.